The Influence of Information Technology and Human Resource Management Capabilities on SMEs Performance - Karnawi Kamar; Novalien Carolina Lewaherilla; Abu Muna Almaududi Ausat; Kurweni Ukar; Silvy Sondari Gadzali (Universitas Dharma Wacana, 2022)
Various efforts have been made by SMEs to be able to survive and get decent performance results in times of crisis by adopting information technology. This is the right innovation step because humans are now interconnected despite the special need for business transformation from traditional to electronic business. However, in its implementation, there are obstacles that hinder the success of the performance results of SMEs that have adopted post-pandemic IT, such as IT capabilities and HR management capabilities. The purpose of this study is to prove and confirm that these two obstacles are real and have been bridged by the local government so that SMEs are not too negatively affected by the pandemic through digital ecosystem training. The object of this research is 66 SMEs in the city of Surabaya. Sampling technique was non-random sampling with type purposive sampling Data was collected by distributing online to selected respondents. The results of the study obtained the fact that IT Capability has a positive and significant effect on the performance of SMEs. This is indicated by the path coefficient value of 0.461 and the P-value of 0.000. Human Resources Management has a positive and significant effect on the performance of SMEs. This is indicated by the path coefficient value of 0.386 and the P-value of 0.000. The calculation results refer to the path coefficient > 0.1 and significant at P-value <0.05. This means that the government's role is highly expected in maintaining the nation's economic stability through the empowerment of SMEs in the aspects of information technology and human resources.